PHYLOGENETIC DIVERSITY OF BACTERIAL POPULATION IN RUMEN - Andreja RAMŠAK; G. AVGUŠTIN (Acta Agriculturae Slovenica)
In order to investigate the microbial diversity in rumen, bacterial 16S rRNA genes were amplified from total microbial DNA isolated from rumen fluid. The amplificated genes were incorporated into pBluescript SK II vector and electroporated into E.coli JM109 cells. The transformants, recognized in hybridization experiments (colony blot) by oligonucleotide DNA probe specific for the Cytophaga-Flavobacterium subgroup of the Cytophaga-Flexibacter-Bacteroides phylum and Prevotella-Bacteroides specific probe, were subjected to the RFLP analysis. On the basis of the RFLP profiles the Jaccard’s similarity coefficients were calculated and the dendrograms were created using the UPGMA method. The representative clones were chosen from the established groups of clones and the 16S rDNA was partially sequenced, compared to already known rRNA sequences in data banks and analysed using Clustal and Phylip phylogenetic packages. A large genetic variability of the rumen bacteria belonging to the Cytophaga-Flexibacter-Bacteroides phylum was established.